2012
DOI: 10.2139/ssrn.1984957
|View full text |Cite
|
Sign up to set email alerts
|

Going Outside the Law: The Role of the State in Shaping Attitudes to Private Acts of Violence

Abstract: Why do people believe that violence is acceptable? In this paper we study people's normative beliefs about the acceptability of violence to achieve social control (as a substitute for the police, for self-protection and the resolution of disputes) and social change (through violent protests and acts to achieve political goals). Addressing attitudes towards violence among young men from various ethnic minority communities in London, we find that procedural justice is strongly correlated with police legitimacy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…These findings match those of the two empirical studies on public support for vigilantism that we found (Tankebe 2009b, Jackson et al 2012b). …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings match those of the two empirical studies on public support for vigilantism that we found (Tankebe 2009b, Jackson et al 2012b). …”
Section: Discussionsupporting
confidence: 91%
“…The study by Jackson et al (2012b), as discussed earlier, suggests that perceived police legitimacy includes the public recognition of police monopoly over violence. Are attitudes towards vigilantism also related to people's respect for the police monopoly on the use of force?…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations